Contact Dermatitis Knowledge Level in Batik Workers of Desa Batik, Tanjung Bumi, Bangkalan, Madura - Prakoeswa, Cita Rosita Sigit; Rahmadewi, Rahmadewi; Setyaningrum, Trisniartami; Damayanti, Damayanti; Anggraeni, Sylvia; Mappamasing, Hasnikmah; Umborowati, Menul Ayu (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Batik has been declared as a humanitarian heritage for oral and non-cultural culture. The increasing demand for batik may have a negative impact as the industry utilizes chemical agents. Hazardous chemical exposure to the skin in the batik industry may result in a high risk of occupational contact dermatitis. This study was conducted to find out the social determinants of health. Purpose: This study aims to assess the level of knowledge of the batik workers before and after health education about occupational contact dermatitis. Methods: This was an observational interview study, and the data were collected using questionnaires. This study involved 30 batik workers.  We assessed the level of knowledge before and after the health education about occupational contact dermatitis. Result: There were 4 (13.3%) male participants and 26 (86.7%) female participants. The mean score of the pre-test was 66.98±10.10, and the post-test was 77.77±13.53 (p<0.05). Conclusion: The result showed a significant difference between batik workers' knowledge before and after health education about contact dermatitis.